An assessment of the terrestrial mammal community in and around Sungai Rawog Conservation Area, Sabah, Malaysia - Henry Bernard; N. Joseph; A. H. Ahmad; S.-L. Kee; Jephte Sompud; M. Nakabayashi; R. Nilus; M.A.F. Suis; J. Miun; H. Miun; R. Jaikim; A. Md. Yakub; et al. (Sabah Forestry Department, 2019)
Sungai Rawog Conservation Area (SRCA), located within the Segaluid Lokan Forest Reserve, is one of the largest wildlife conservation areas set aside in an active production forest reserve in Sabah, Malaysian Borneo. However, much remains unknown about its animal communities. We conducted a mammal survey in and around the SRCA to gather baseline data on animal community structure and to inform conservation management strategies for this area in general. Between July 2018 and February 2019, we used camera traps (total camera trapping effort: 855 camera trap-days), in addition to day transect surveys, night roadside spot light surveys and other incidental sightings, which led to the detection of 32 mammal species from 8 orders. These included common and rare species, as well as species of high conservation value, such as bearded pig (Sus barbatus), sambar deer (Rusa unicolor), banteng (Bos javanicus), Asian elephant (Elephas maximus), orang-utan (Pongo pygmaeus morio), Sunda clouded leopard (Neofelis diardi), flat-headed cat (Prionailurus planiceps) and Malayan pangolin (Manis javanica). Photographs captured of the flat-headed cat from our study may likely be the first photographs of this species taken from the SRCA, hence confirming the presence of this extremely rare wild cat species in Segaliud Lokan FR. Despite the highly disturbed nature of the forests due to past logging activities, the surveyed sites in and around the SRCA serve as important habitats and provide a functional protected conservation area for many important animal species. We conclude that the conservation of the SRCA is vital for the continued survival of the animal communities in this region of Sabah and suggest the need for long-term protection, research and monitoring programmes of the habitats and animal communities.